Uji Aktivitas Antijamur Minyak Atsiri Bunga Kenanga (Cananga odorata) sebagai Sampo Antiketombe Terhadap Pertumbuhan Jamur Pityrosforum ovale dan Jamur Malassezia furfur secara In-Vitro - Nasution, Annisa Puji Astuti; Rasyidah, Rasyidah; Mayasari, Ulfayani (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This study aims to determine the activity of natural anti-dandruff shampoo, ylang-ylang flower essential oil (Cananga odorata) on the growth of Pityrosforum ovale and Malassezia furfur fungi in vitro. The method used in making ylang ylang (Cananga odorata) flower essential oil uses steam distillation, and the antifungal activity test uses the disc diffusion method with concentrations of 30%, 40%, 50%, and 60%. Test results use Analysis of Variance (ANOVA). The results of the study showed that there was antifungal activity of anti-dandruff shampoo of ylang-ylang flower essential oil (Cananga odorata) against the fungus Pityrosforum ovale and Malassezia furfur fungus with a significant value of p < 0.05. The results of theactivity test of the natural anti-dandruff shampoo of ylang-ylang flower essential oil (Cananga odorata) used concentrations of 30%, 40%, 50%, and 60%, the diameter of the fungal inhibition zone obtained from Pityrosforum ovale are 16.28 mm, 19.66 mm, 20.0 mm, and 20.1 mm. Meanwhile, the test results for the diameter of the inhibition zone on the Malassezia furfur fungus were 16.5 mm, 20.41 mm, 20.53 mm, and 21 mm. In conclusion, the results of the average antifungal activity of the inhibitory zone of ylang-ylang flower essential oil (Cananga odorata) can be used as an anti-dandruff shampoo against the fungus Pityrosforum ovale and the fungus Malassezia furfur at an effective concentration of 30%. Keywords: Malassezia furfur, Essential Oils, Pityrosforum ovale, Anti-Dandruff Shampoo